Chinese geopolitical goals in the Arctic - I. S. Doroshenko (Проблемы постсоветского пространства, 2019)
The People’s Republic of China is increasing its influence around the world every day. It’s hard not to notice the aggressive economic expansion being carried out by China in the Asian region. Chinese presence is felt in Africa, South America and even in Europe. By engaging in a trade war with the United States, China thereby challenged the most influential economy in the world, which is confirmed by its ambitions as a world leader. To meet these ambitions, a powerful transport and logistics support is necessary, which gave rise to the “Belts and Ways” initiative. The initiative “One Belt - One Road” combines two projects: “The Economic Belt of the Silk Road” and “The Sea Silk Road of the XXI Century”. This means that, in addition to the traditional land routes of the Silk Road, Beijing is exploring the sea routes along the African continent and in the Pacific Ocean. Since the initiative does not have a clear strategy, the northern routes that have recently become relevant are also considered by the Chinese authorities.The search for an alternative to the Suez Canal has repeatedly prompted researchers to use the Northern Sea Route as a trading artery linking Europe and Asia, but climatic conditions and technical capabilities did not allow this idea to be realized. The current situation in the Arctic region allows us to talk about new development prospects.China is actively interested in the Arctic: since 2013, it has an observer status in the Arctic Council, has been increasing its presence in the region by organizing scientific expeditions, building icebreakers, introducing its own brand “Northern Silk Road”, and also investing in projects like “Yamal LNG». China outlined its presence in the Arctic region in a white paper published in January 2018. One of the main goals that Beijing sets for itself is multilateral cooperation in the development of the Northern Sea Route.The author of the article analyzes the origins of such interest, as well as possible threats to Russia. The study also examines the position of European partners in the participation of the development of the SMP, bilateral relations with the Chinese side and the ratio of the strategy of the European Union, China and Russia in the High North. The author gives a geopolitical rationale for Chinese initiatives that are aimed at creating the conditions for intensive navigation in the northern areas.